SUPPLY CHAIN MANAGEMENT IN THE MEDICAL TOURISM NETWORKING SYSTEM: A REVIEW - Harahap, Lia Adelina (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2023)
The science development in the medicine field, brings the new methods and systems for health care and medical treatment, and also brings the convenience in transportation and communication. Accordingly, a new field of tourism emerges, that is the medical tourism. Medical tourism is an emerging tourism trend that has recently gained increasing popularity. The idea of medical tourism is that when individuals travel abroad to seek for medical services while at the same time have the intention of healing and relaxation. In practice, this particular field involves many stakeholders that collaborate each other to serve the customer. Consequently, the medical tourism industry depends mainly on the networking system. For that reason, one of the most beneficial management methods for coordinating and integrating these relevant parties in this particular field is through Supply Chain Management (SCM) in that SCM covers the management of numerous activities multiple role-players from various divisional functions and organizations. Accordingly, this paper aims to explore the system that supports medical tourism, particularly by searching the literature and sources of information related to this particular field. Several selected studies suggested a medical tourism supply chain conceptual model to develop better understanding of medical tourism system as a whole.